Improving intergroup relations between Catholics and Protestants in Northern Ireland via e-contact - White, FA; Turner, RN; Verrelli, S; Harvey, LJ; Hanna, JR (Wiley, 2018)
Northern Ireland is characterised by extensive segregation between its predominantly Catholic and Protestant communities. With the aim of overcoming this segregation, the current study experimentally evaluated the effectiveness of electronic or E‐contact as a novel indirect contact and prejudice‐reduction strategy. Here, Catholic and Protestant participants were not required to meet physically but were involved in a collaborative and goal‐orientated online interaction with a member of the other community. As predicted, E‐contact improved both Catholics’ and Protestants’ outgroup attitudes via improved contact expectancies and reduced intergroup anxiety. These findings provide support for the contemporary role of online interactions in actively overcoming the physical and psychological barriers that often prevent prejudice reduction in segregated communities.